UPAYA MENINGKATKAN KERJASAMA MELALUI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA ANAK USIA 5-6 TAHUN - Iin Khoirinnisa; Nahdiyah Hidayah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The low cooperative skills of 5-6 year old children at the Putra Parikesit Kindergarten are the background of this study, characterized by selfish behavior during play and difficulty sharing. The focus of the study was directed at improving these social skills through the Team Games Tournament (TGT) cooperative model. This study used the Kurt Lewin Classroom Action Research design model which includes two systematic cycles including planning, action, observation, and reflection. Quantitative data from observations showed a significant increase in three main indicators. The ability to build good relationships increased from an initial condition of 35% to 75% in the first cycle, and reached 90% at the end of the second cycle. The emotional control indicator also increased from 25% to 80%, while the sense of responsibility developed from 35% to 85%. The research findings revealed that the elements of healthy competition and team play in TGT can trigger enthusiasm and collective awareness in children to help each other and communicate positively. The main conclusion confirms that the TGT model has proven to be very effective as an innovative strategy in optimizing the social-emotional development of early childhood. The implementation of this model has successfully transformed the classroom atmosphere to be more active, harmonious, and collaborative, so it is worthy of being used as a reference for educators to build children's cooperative character through a systematically planned play-while-learning method to ensure the achievement of collective social moral indicators.